PENINGKATAN KETERAMPILAN AI (ARTIFICIAL INTELLIGENCE) DALAM DUNIA TELEKOMUNIKASI DIGITAL PADA TENAGA PENGAJAR SEKOLAH KEJURUAN TJENDEKIA PURUHITA SEMARANG - Muliandhi, Puri; Cahyono, Taufiq Dwi; Nihayah, Rofi'atun (TEMATIK, 2021)
Tjendekia Puruhita Vocational School is a school located in the City of Semarang. Tjendekia Puruhita Vocational School Semarang has a media website and also other social media to provide information to the surrounding community. The ability of digital media managers to compile content can better convey messages to the public. This is of course necessary for the managers of the Tjendekia Puruhita Vocational School.The problem faced by the Tjendekia Puruhita Vocational School Semarang is that the Tjendekia Puruhita Teachers have not mastered AI (Artificial Intelligence) telecommunications in the Digital World. Based on this, we strive to hold Tjendekia Puruhita Semarang Vocational School with the aim of improving AI (Artificial Intelligence) Telecommunication skills in the Digital World for Tjendekia Puruhita Vocational School Semarang. The output of this activity included an increase in the understanding and skills of AI (Artificial Intelligence) telecommunications from the teaching staff at the Tjendekia Puruhita Vocational School, Semarang. Keywords: Telecommunications, Artificial Intelligence, Digital Media.